Analyzing the Causal Relationship Between Tax Avoidance and Earnings Management: Evidence from The STOXX Europe 600 Index - Olfa Ben Salah (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- Can a bidirectional link be established between earnings management and tax avoidance? Motivation- The relationship between tax avoidance and earnings management has been a subject of significant scholarly interest, yet it remains inconclusive and context-dependent. Idea- This study seeks to examine the bidirectional causality between tax avoidance and earnings management. Data- The author selected companies listed on the European STOXX 600 index for the period from 2010 to 2022. Tools- To test the research hypothesis, the author employs the Granger causality procedure on panel data and applies a dynamic panel using the Generalized Method of Moments (GMM) approach. Findings- The results of our study indicate a bidirectional causal relationship between tax avoidance and earnings management in the European context. Contribution- Our research contributes to the existing literature by shedding light on the nuanced relationship between tax avoidance and earnings management in the European context, offering insights that can inform corporate financial strategies and regulatory frameworks.
Keywords: H26; M41; 650; Earnings management; Tax avoidance; Bidirectional causality; Granger-causality